Finance and Development, September 1976. (Finance and Development; Finance and Development, 1976)
This paper highlights that the IMF, as Trustee for the Trust Fund, held the first of its series of gold auctions on June 2, 1976, with the sale of 780,000 ounces of gold-the total amount offered-at a common price of USD 126.00 a fine ounce. The first gold auction was a success from the point of view of both the market and the IMF. In all, a total of 25 million ounces of gold from the IMF's holdings will be sold at auction over a four-year period.